A FRAMEWORK STRATEGY FOR SUSTAINABILITY CONSTRUCTION WASTE MANAGEMENT: CASE OF WEST BANK, PALESTINE - Hareez, Firas (An-Najah National University, 2024)
This study aims to develop a strategic framework for sustainable construction and demolition (C&D) waste management in the West Bank of Palestine. Currently, no regulatory system governs C&D waste, resulting in unsustainable practices like dumping and burning that degrade the environment and public health. Previous research provided initial estimates of waste quantities, but gaps remain regarding generation patterns, stakeholder roles, and barriers. The research uses a mixed-methods approach, including questionnaires with 100 professionals and interviews with 10 interviewees. Secondary data from literature and reports supplements the Analysis. Findings show a lack of on-site segregation and essential management, 35% of the debris was dumped and more than 5% of the debris was burned illegally. Joint Service Councils manage collection and disposal but have limited capacity and funding. Political fragmentation also complicates coordination. Significant barriers include inadequate policies, infrastructure, lack of private sector compliance, and socioeconomic pressures. Study proposes a strategic framework to address these challenges to establish a coordinated C&D waste governance system by 2027. Objectives focus on strengthening regulations, improving on-site practices, developing infrastructure networks, boosting reuse/recycling markets, and creating sustainable financing mechanisms. A phased implementation plan outlines priority actions, responsibilities, and timelines for stakeholders to transition the sector toward sustainability. The framework provides a roadmap to guide reforms and capacity building needed to manage C&D waste responsibly in the West Bank.
اطار استراتيجي للإدارة المستدامة لمخلفات البناء: حاله في الضفة الغربية في فلسطين